Noonan's Syndrome. Case Report - Mirsa Rosas Hernández; Elba Daisy Rivas Rodríguez; Raúl E. Silva Silva (Medisur, 2015)
Noonan's syndrome is a genetic, little-known disease, produced for a mutation in the 12q22 chromosome. Few data on this affection exists in Cuba; since studies with a significant sample have not been conducted that demonstrate the real frequency of the affection. An eight year old patient’s case from Banes, Holguín, is presented, to whom the syndrome through comparative technique was diagnosed, and considering the clinics and radiological characteristics. The consent of parents to do and to divulge this report was taken into account. The interest of this case consists on the low frequency of appearing of Noonan's syndrome, in fact, the first one that has been diagnosed at the municipality.